Age‐specific 3‐year cumulative risk of cervical cancer and high‐grade dysplasia on biopsy in 9434 women who underwent HPV cytology cotesting. Issue 12 (7th October 2019) - Ge, Yimin; Christensen, Paul A.; Luna, Eric; Armylagos, Donna; Xu, Jiaqiong; Hsu, Jim W.; Zhou, Haijun; Schwartz, Mary R.; Mody, Dina R.
Abstract : Background: High‐risk human papillomavirus (HPV)–Papanicolaou (Pap) cotesting is recommended for cervical cancer screening in women aged ≥30 years. The current study analyzed the effectiveness of cotesting on risk management in different age groups. Methods: A retrospective review of a 5‐year cytology database identified 9434 women with HPV‐Pap cotesting and follow‐up cervical biopsy. The 3‐year cumulative risk of developing high‐grade cervical lesions (≥high‐grade squamous intraepithelial lesion [HSIL]) was analyzed using age stratification. Results: The 3‐year cumulative risk of developing ≥HSIL was found to be significantly different in women with baseline cotesting HPV‐positive and Pap‐positive results (HPV+/Pap+; defined as ≥atypical squamous cells of undetermined significance), HPV+ and Pap‐negative results, and HPV‐negative and Pap+ results at 19.2%, 7.9%, and 3.1%, respectively ( P < .001). The risk of ≥HSIL peaked at ages 30 to 39 years and significantly decreased at ages 50 to 59 years (16.6% vs 6.7%; P < .001). Women aged <30 years shared a high risk similar to that of women aged 30 to 39 years (17.3% vs 16.6%; P = .52), and risk stratification by cotesting was found to be equally effective in the younger age group (HPV+ and Pap+: 19.6%; HPV+ and Pap‐negative: 7.2%; and HPV‐negative and Pap+: 4.4% [ P < .001]). Conclusions: High‐risk HPV–Pap cotesting appears to be extremely sensitive for the prediction of the risk of developing ≥HSIL and is an effective tool for risk stratification. In the current study, the 3‐year cumulative risk of developing ≥HSIL varied significantly with age, with the highest risk noted among women aged <40 years and the lowest risk observed in women aged 50 to 59 years. Pap testing significantly impacted risk stratification in the HPV+ positive group, especially in women aged <60 years. Women aged <30 years were found to have a risk profile and cotesting efficacy similar to those of women aged 30 to 39 years. Modification of the current recommendation to offer cotesting to women aged ≥30 years might be considered to include those patients aged <30 years. Abstract : Papanicolaou tests have a significant impact on risk stratification in women with positive high‐risk human papillomavirus tests, which appears to be most striking in younger age groups. Women aged <30 years share a risk profile similar to that for women aged 30 to 39 years, with cotesting appearing to be equally effective in both groups. Offering cotesting to women aged <30 years may be beneficial.